Social Anthropology in Lithuania: Challenges, Resilience, and Particularity of the Discipline - Čiubrinskas, Vytis (Vilnius University Open Series, 2025)
The discipline of sociocultural anthropology has particular connotations in Central and Eastern Europe. German scholarly contributions played a major role in setting the academic agendas for its development in this European region. Herder’s “recognition of the unique spirit of each people, conceived of as a separate organism, developing according to its own specific trajectory” made a synonym of the terms nation and folk (Hann 2007) and laid the ground for ‘studying peoples’, first of all in Germany, defined differently, as just peoples (Völkerkunde) and as those peoples who do belong to a nation as folk (Volkskunde). Such a division had a lasting effect on scholarship in Central and Eastern Europe during the era of nationalist mobilization, which followed the collapse of the region’s empires in the nineteenth century and the Soviet bloc at the end of twentieth century. The aim of this paper is to try to unpack the influence of the dominant discourses and national identity politics on the research and teaching strategies of the discipline of anthropology in Lithuania. It is a participant informed reflection on the development and professional practicing (by teaching and doing research) of this discipline in the course of the ongoing social and institutional changes in the country during the last three decades.